Estrategias innovadoras en el desarrollo de la pre escritura - Chanchicocha Chillagana, Mónica Cecilia (2016)
This research was conducted at the Education Unit Alicia "Marcuard of Yerovi" of Salcedo Canton in the school year 2015 -2016, the interest that led her to make some research was when I was shown that children 3rd year EGB had problems when holding the pencil, and strong grip when writing, writing in poor condition and lack of interest in performing their tasks, ie children lacked appropriate to their age from baseline activities develop fine motor skills, then what is tried is to discover what is the central point of that problem that children possess. With the following theme "Innovative Strategies in the development of the Pre writing with children 4 to 5 years for the initial level II, for which surveys was applied to teachers of initial level II and first year EGB and chips observations result It was obtained that need innovative strategies to develop their motor skills and that there is a pre-concentration by the school at the time of writing pre strokes. The objective of this research is to determine the importance of activities prewriting to develop fine motor skills by Innovative Strategies and prevent difficulties in motor skills, improving oculus manual coordination in the infant, this from inviting teachers ha.: You look, apply new learning methodologies. As evidence of this research they were collected professional criteria and determined that children that are very ingenious in the teaching-learning process should be encouraged correctly; that teachers are aware of the teaching and learning processes and strategies to be applied to children in a didactic way, focusing on innovative activities that help the school in the development of prewriting, so that students reach succeed in their school life, be creative and self-confident human talent.